P62 Early Results of a National Lung Cancer Awareness Campaign. (19th November 2012) - Maguire, J; Kelly, V; Ledson, M; Smyth, C; McIver, A; Walshaw, M
Abstract : In May 2012 a centrally funded National Lung Cancer Awareness Campaign was initiated. This campaign was influenced by encouraging results from local pilot studies, and featured news items and public health awareness adverts in national and local media, including nationwide television and radio exposure, accompanied by celebrity involvement and endorsements. The cost of this initiative has not been disclosed. Liverpool has the highest lung cancer incidence and mortality in England, and our Lung Cancer Unit, providing a service for patients in South Liverpool, is the largest in the Cancer Network and amongst the largest in the country. To assess the impact of the national campaign we have reviewed referrals to our Rapid Access Lung Cancer Service from General Practise via the 14 day suspected cancer pathway, during the months of April, May and June 2012; we have also reviewed referrals during the same months in 2011 and 2010. The total number of referrals from General Practise was 20 in April 2012, 30 in May 2012 and 27 in June 2012. The proportion of patients who had lung cancer was 8/20, 15/30 and 11/27 respectively. The percentage of patients with a diagnosis of lung cancer who underwent potentially curative surgical resection was 25% in April, 30% in May and 27% in June. Comparison with corresponding figures from 2011 and 2010 shows no significant difference in lung cancer referral or diagnosis rates, with a small but not statistically significant increase in surgical resection rates year on year. Our conclusion is that the national awareness campaign initiated in May 2012 has had no significant early effect on lung cancer referral, diagnostic and treatment patterns in our area.